"تحسين مهارات الطلاب في إنشاء جمل بسيطة دقيقة باللغة العربية باستخدام "قوالب كاندي: Improving Students' Skills in Creating Accurate Simple Arabic Sentences using Qawalib Candy - Abdul Karim, Nurul Syfiqah (SIBAWAYH Arabic Language and Education, 2024)
البحث يهدف إلى تقييم فعالية استخدام "قوالب كاندي" كوسيلة تعليمية مبتكرة في تعليم اللغة العربية، وتحديداً في تمكين الطلاب من تكوين جمل صحيحة وذات بنية لغوية سليمة. تضمنت الدراسة عينة من 20 طالباً من الصف الثالث في إحدى مدرسة الثانوية بمنطقة كلانج سلانجور، والذين يعانون من صعوبات في تركيب الجمل بطريقة سليمة. ترتكز "قوالب كاندي" على بطاقات تعرض تراكيب جملية ومفاهيم لغوية تساعد على تعزيز الفهم النحوي. أظهرت نتائج الدراسة أن هذه القوالب تسهم بشكل فعّال في تعزيز مهارات الطلاب في إنشاء جمل عربية صحيحة وتحسين فهمهم للتراكيب النحوية الأساسية والمعقدة على حد سواء. وقد تبيّن أن هذه الأداة التعليمية لا تسهم فقط في التطبيق العملي لقواعد اللغة، بل تعزز أيضاً إتقان الطلاب للمفاهيم النحوية بشكل عميق، مما يجعلها أداة قيّمة في سياق تعليم اللغة العربية على مستوى التعليم الثانوي.The research aims to evaluate the effectiveness of using "Candy Templates" as an innovative educational tool in teaching the Arabic language, specifically in enabling students to construct correct and linguistically sound sentences. The study involved a sample of 20 third-grade students from a secondary school in Klang, Selangor, who experience difficulties in constructing sentences correctly. "Candy Templates" are based on cards that present sentence structures and linguistic concepts to help enhance grammatical understanding. The study's results showed that these templates effectively contribute to improving students' skills in creating correct Arabic sentences and enhancing their understanding of both basic and complex grammatical structures. It was found that this educational tool not only aids in the practical application of language rules but also strengthens students' mastery of grammatical concepts, making it a valuable tool in the context of Arabic language education at the secondary school level.Keywords: Effectiveness, Instructional Tool, Sentences, Cards, Sentence Structures, Skills